https://doi.org/10.36873/ PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L) TERHADAP PEMBERIAN BIOCHAR SEKAM PADI DAN BOKASHI KALAKAI PADA TANAH SPODOSOL: Application of Rice Husk Biochar and Kalakai Bokashi for Increasing The Growth and Yield of Onion on Spodosol - Y Kharisma; Syahrudin Syahrudin; Untung Darung; Kambang Verani Asie (AgriPeat, 2021)
The purpose of this experiment were to find out the interaction growth and yield of onion (Allium ascalonicum L) on the giving of rice husk biochar and kalakai bokashi for increasing the growth and yield of onion on spodosol. This study used Completely Randomized Design (CRD) of factorial pattern with two factors. The first factor was applying of rise husk biocar (B) consisting of 4 (four) levels, namely : B0 = 0 ton.ha-1, B1 = 6 ton.ha-1 , B2 = 9 ton.ha-1 and B3 = 12 ton.ha-1 . The second factor was the provision of bokashi kalakai (K) which consists of 4 (four) levels, namely : K0 = 0 ton.ha-1 , K1 = 15 ton.ha-1, K2 = 20 ton.ha-1 dan K3 = 25 ton.ha-1. The results showed the interaction of the rice husk biochar and kalakai bokashi have an effect heavy dry bulbs. The combination of rice husk biochar treatment (B3) 12 ton.ha-1 and bokashi kalakai (K3) 25 ton.ha-1 was able to increase the yield of onion with the yield of tuber dry weight of 45.33 g.plant -1